(untitled) (Fiep Bulletin - online, 2015)
This piece of work analyzed the capacity of the elderly to perform everyday activities.. To do so, three tests were applied which assess such capacity (AVD’s), which were: Test to sit down and stand up from the chair and move around the house ; Test to put on a pair of socks and, time oneself after moving 800 metres”. Thirty people were tested, being all women, physically independent. These participants are part of the UNI-BH maturity laboratory. They went through the tests in two stages, split in 6 weeks of physical activities. The classes took place three times a week, each class lasted for 2 hours and the aims were the improvement of the coordination, the balance, heart beating capacity and flexibility. The results showed significant improvement in the execution of AVD’s after the regular practice of recreational physical activities. We cocluded that the physical activity is a fundamental factor for the elderly to have his physical independence.